A comparative study of head morphology shape between Sibrean sturgeon (Acipenser baerii), Beluga sturgeon (Huso huso) and their diploid and triploid hybrids (male Siberian sturgeon × female Beluga) using geometric morphometrics technique - Eshagh Zadeh, Hamid (2015)
Polymorphism between the species of sturgeons due to natural hybridization, human manipulations and escaping hybrids from farms makes their identification difficult. Hence, this research was conducted to study the differences in head shape between the Great beluga (Huso huso), Sibrean sturgeon (Acipenser baerii) and their diploid and triploid hybrids (male Siberian sturgeon × female Beluga) using geometric morphometric technique. In total 120 specimens (30 specimens from each group) were sampled. Nine, twelve and thirteen land mark points were digitized on 2D images of the lateral, dorsal and ventral views of their head, respectively, usingTpsDig2. Landmark data after GPA, was analyzed using CVA and MANOVA.The results showed significant differences the terms of head shapes in all three views (P<0.001). Based on Mahalanobis distances, the shape of head inventral view has better ability to differentiate the species and their diploid and triploid hybrids. The results also showed that hybrids head shape are more similar to male parent. This study confirmed the ability of geometric morphometrics method as an effective, standard and low cost technique to identify sturgeon species and their hybrids. Published